(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This work explores the phenomenon of borrowing words in the Russian and Uzbek languages, analyzing the history and meaning of borrowed words for both languages and their impact on the lexicon and cultural heritage. The work examines the process of borrowing words from various languages (Greek, Latin, Arabic, Persian, French, etc.) and provides examples of borrowed words in the Russian and Uzbek languages. Similarities and differences in the use and pronunciation of borrowed words are analyzed, and the influence of cultural contacts on the borrowing process is considered. The work consists of conclusions about the importance of borrowed words for enriching the lexicon and cultural heritage of both languages, and also offers prospects for the development of borrowed words in the Russian and Uzbek languages.